A game plan for the resumption of sport and exercise after coronavirus disease 2019 (COVID-19) infection - Phelan, D.; Kim, J. H.; Chung, E. H. (JAMA Cardiology, 2020)
Coronavirus disease 2019 (COVID-19) is associated with significant mortality and morbidity, including adverse cardiovascular sequelae.1 As public health policy begins to guide the resumption of recreational and competitive sport, clinicians are charged with determining when competitive athletes and highly active individuals who have been infected with COVID-19 and recovered are medically appropriate to return to play. There are limited data establishing the epidemiologic and clinical metrics required to facilitate this process. Specifically, the prevalence of asymptomatic COVID-19 cases in the community, the prevalence of cardiac injury among nonhospitalized individuals with COVID-19, and long-term outcomes attributable to COVID-19 cardiac injury remain unknown. Recognizing these limitations, members of the American College of Cardiology`s Sports & Exercise Cardiology Council, with input from national leaders in sports cardiology, provide a consensus expert opinion clinical framework on return to play in the era of COVID-19.